Acupoint Injection Combined with BCG-PSN and Thymosin Enteric-Coated Tablets Improve China Han Psoriasis Vulgaris by Regulating T Cell Subsets - Li J; Zhao X; Pan H; Duan Y; Li W; Zhao Y; Yao L; Zhang K (Psoriasis: Targets and Therapy)
Junqin Li,1 Xincheng Zhao,1 Hong Pan,1 Yanping Duan,2 Wen Li,1 Yanhong Zhao,1 Lifeng Yao,1 Kaiming Zhang1 1Shanxi Key Laboratory of Stem Cells for Immunological Dermatosis, Institute of Dermatology, Taiyuan City Central Hospital, Taiyuan, 030009, People’s Republic of China; 2Department of Acupuncture and Massage, Taiyuan City Central Hospital, Taiyuan, 030009, People’s Republic of ChinaCorrespondence: Kaiming Zhang, Taiyuan City Central Hospital, No. 5 Dong San Dao Xiang, Jiefang Road, Taiyuan, 030009, People’s Republic of China, Tel +86-0351-5656080, Email zhangkaiming@sina.comPurpose: Psoriasis is a common chronic inflammatory skin disease. Acupoint injection is reported to be used for the treatment of psoriasis, however its mechanism is not yet clear. The study aimed to investigate the efficiency of combined treatment including acupoint injection in the treatment of psoriasis.Patients and Methods: Here, we compared the efficacy of multiple immune intervention therapy (MII, acupoint injection with BCG-PSN combined with thymosin enteric-coated tablets, levamisole, intramuscular injection with BCG-PSN) to NB-UVB and acitretin for psoriasis. One thousand two hundred patients with moderate-severe psoriasis vulgaris were randomly treated with MII, NB-UVB or acitretin. For another 53 patients treated with MII, the T cell subsets and TCR repertoire analysis were investigated with sequencing and flow cytometry.Results: The effective rate in MII treated group was similar to acitretin-treated group in 3 months (P > 0.05), though lower than in subjected treated with NB-UVB (P < 0.05). MII treatments maintained a longer remission of both PASI25 and PASI75 in comparison to the treatment with either NB-UVB or acitretin in following 5-year follow-up. Moreover, the relapse rate was lower in MII treatment than in either NB-UVB (P < 0.0001) or acitretin treatment (P < 0.0001), accompanied with longer remission duration (MII vs both NB-UVB and acitretin, P < 0.0001). Meanwhile, MII treatments markedly increased Treg cells (P = 0.04), while decreasing the number of both Th1 (P < 0.001) and Th17 cell (P = 0.01), along with decreased secretion of IFN-γ (P = 0.03) and IL-17 (P = 0.02). Multivariable Cox regression analysis demonstrated that MII significantly reduced psoriasis relapse risk versus NB-UVB (58.7% reduction; HR = 0.413, 95% CI: 0.329– 0.517, P < 0.001) and acitretin (65.3% reduction; HR = 0.347, 95% CI: 0.276– 0.435, P< 0.001).Conclusion: Acupoint injection combined with BCG-PSN, thymosin enteric-coated tablets and levamisole treat psoriasis and prevent relapse of psoriasis, via modulation of Treg/Th1/Th17.Keywords: acitretin, acupoint injection, NB-UVB, psoriasis vulgaris, T cell subsets